Position before submission? Techniques and tactics in competitive no-gi Brazilian jiu-jitsu - Charalampos Spanias; Christopher Kirk; Karsten Øvretveit (Universidad de León, 2022)
Brazilian jiu-jitsu (BJJ) is a grappling-based combat sport performed either with a traditional uniform, the gi, or without, known as no-gi. Differences between the two when it comes to gripping, pace, and ruleset can affect match characteristics, which has implications for how athletes approach competition. The present study investigated time-motion and technical-tactical characteristics in matches from official no-gi submission-only BJJ tournaments. The analysis included 26 regional and 26 international athletes from the light-feather to super-heavy weight class. Match characteristics did not differ between competition levels, style (guard or pass player), or weight (p > 0.05). The duration of positional dominance was similar between competition levels and styles (p > 0.05), but significantly different between winners and losers (p < 0.05; effect size (ES) = 0.39). Positional dominance also correlated with upper-body submissions (r = 0.50; p < 0.05). Interestingly, positional dominance appeared inconsequential in matches determined by lower-body submissions. In fact, athletes winning by lower-body submissions, in most cases a heel hook, exerted no positional control prior to their victory. The high- to low-intensity ratio was 1:2 and 1:1, for regional and international athletes, respectively. The standing to ground time ratio was 1:2 for both groups. In addition to the novel competition characteristics of competitive no-gi BJJ, these findings indicate that there are strategical discrepancies that precede distinctly different submission holds.